Fuzzy AHP, RS & GIS Based Hybrid Approach for Airport Site Selection-Kothagudem District - Keshav M, Penki Ramu, Srinivasarao T, Lalith Nandan K (International Journal of Advanced Science and Technology, 2020)
Airport plays a major role in the development of economy. Air transportation has the highest speed among all modes of transportation, offering an unbroken journey over land and sea. This study makes use of Geographic Information Systems (GIS) and a Multi Criteria Decision making Methodology (MCDM) i.e., Analytical Hierarchy Process (AHP) and FAHP for selection and ranking of various available airport sites in the entire kothagudem district region and further evaluation of available sites by considering various factors of selection which are traditionally used. AHP and FAHP are MCDM techniques in which various criteria are weighed on a scale of 1 – 9 based on their importance in selection of final choice. Various criteria used in this study are distance from roads and railway networks, distance from agriculture, distance from forest, distance from a water bodies, and distance from built-up area. Thematic maps were created for each criterion by performing spatial analysis in GIS. These maps were reclassified using the weights derived from AHP approach and FUZZY (degree of truth) are used in overlay analysis for obtaining the suitability index of various sites present over the entire district region. This study suggests that GIS, FUZZY and AHP are useful techniques for identification and evaluation of site selection compared to traditional methods. The suitability index is found to be in the range of 0-41.92% from FAHP and 0-41.52% from AHP, which indicates the lack of highly suitable spaces in the study region.